2014
DOI: 10.4238/2014.april.3.18
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic classification and clinical aspects of a new putative Deltapapillomavirus associated with skin lesions in cattle

Abstract: ABSTRACT. Bovine papillomaviruses (BPVs) are recognized as causal agents of benign and malignant tumors in cattle. Thirteen types of BPVs have already been described and classified into 3 distinct genera. Divergences in the nucleotide sequence of the L1 gene are used to identify new viral types through the employment of PCR assays with degenerated primers. In the present study, a method for identifying BPVs based on PCR-RFLP and DNA sequencing allowed the identification of a new putative Deltapapillomavirus, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
2
15
0
2
Order By: Relevance
“…We have studied the herd from which samples were obtained for the present study for the last 3 years, and have observed similar results to those reported in the literature (Araldi et al, 2013;Melo et al, 2014). A high incidence of cutaneous papillomatosis was observed in the herd studied, mainly in younger bovines of 2-3 years of age.…”
Section: Molecular Diagnosis and Histopathological And Immunohistochesupporting
confidence: 85%
“…We have studied the herd from which samples were obtained for the present study for the last 3 years, and have observed similar results to those reported in the literature (Araldi et al, 2013;Melo et al, 2014). A high incidence of cutaneous papillomatosis was observed in the herd studied, mainly in younger bovines of 2-3 years of age.…”
Section: Molecular Diagnosis and Histopathological And Immunohistochesupporting
confidence: 85%
“…In the epidermis, mild to severe acanthosis, hyperkeratosis, prominent parakeratosis, mild to moderate basophilic cytoplasmic swelling, vacuolar degeneration of keratinocytes, and many koilocytes (including keratohyalin granules) were present. Moreover, similar histopathologic features in BPV infection have been previously reported in cattle from Brazil (15,23,24) and from Italy (17,25), and in water buffaloes and cattle from Turkey (19)(20)(21) and from India (26).…”
Section: Discussionsupporting
confidence: 52%
“…Although the identification of BPV types and epidemiological and clinical studies have provided new insights for the prevention and therapeutic procedures of papillomavirus infections (15), little is known about the presence of BPV in Turkey, except Deltapapillomavirus (BPV-1 and BPV-2) (19)(20)(21). The objective of the present study was to screen for the presence of different BPV types in cattle with papillomatosis as well as in healthyappearing cattle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplicons obtained were sequenced and virus typing showed the presence of BPV-2 in sample 1 (99% identity), BPV-11 in sample 2 (99% identity) and a new putative virus type in sample 3 (Figure 1). This new putative virus type was identified as BPV-JN/3SP (GenBank JQ280500.1) and was already described by Melo et al (2014). However, it was not possible to detect BPV with the FAP59/FAP64 primers in blood samples.…”
Section: Molecular Identification and Typing Of Bpv In Tissue And Blomentioning
confidence: 99%